A Review on Synchronous Microalgal Lipid Enhancement and Wastewater Treatment - Visva Bharati Barua; Mariya Munir (Energies, 2021)
Microalgae are unicellular photosynthetic eukaryotes that can treat wastewater and provide us with biofuel. Microalgae cultivation utilizing wastewater is a promising approach for synchronous wastewater treatment and biofuel production. However, previous studies suggest that high microalgae biomass production reduces lipid production and vice versa. For cost-effective biofuel production from microalgae, synchronous lipid and biomass enhancement utilizing wastewater is necessary. Therefore, this study brings forth a comprehensive review of synchronous microalgal lipid and biomass enhancement strategies for biofuel production and wastewater treatment. The review emphasizes the appropriate synergy of the microalgae species, culture media, and synchronous lipid and biomass enhancement conditions as a sustainable, efficient solution.